Chapter Bruno Trentin: una biografia attraverso l'Archivio Storico della CGIL - Romeo, Ilaria (Studi e saggi, 2023)
The intellectual, political and human story of Bruno Trentin emerges from the paper and multimedia documentation related to him preserved by the National CGIL Historical Archives. Documents and images narrate the France of exile, Padua, a university city in which the Resistance was active, partisan Milan, and Fiat Mirafiori blocked by strikes, but also Trentin's commitment and charisma in his roles as a young researcher in the confederal study office, Fiom secretary, national and general secretary of the CGIL, and European parliamentarian for the PDS in the 1999-2004 legislature. Images from the photographic fund and paper records document his relationships with, among others, European Commission President Delors, Brazil's President Lula, South Africa's President Mandela and Solidarity leader Walȩsa.